2012
DOI: 10.5301/jn.5000153
|View full text |Cite
|
Sign up to set email alerts
|

Women on hemodialysis have lower self-reported health-related quality of life scores but better survival than men

Abstract: Women on hemodialysis had more depression-related symptoms and poor self-reported HRQoL, but better survival than men. The sex difference in psychological and HRQoL issues deserves greater concern because this relates to clinical care and further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 39 publications
3
15
1
4
Order By: Relevance
“…This finding corroborates Lew-starowicz's findings showing that women who are undergoing hemodialysis and have lower sexual function index also have lower quality of live [27 ] a finding recently confirmed by Peng and al [28]. It seems that a part of somatic, mental and social health of women is related to their sexual function and marriage relations.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding corroborates Lew-starowicz's findings showing that women who are undergoing hemodialysis and have lower sexual function index also have lower quality of live [27 ] a finding recently confirmed by Peng and al [28]. It seems that a part of somatic, mental and social health of women is related to their sexual function and marriage relations.…”
Section: Discussionsupporting
confidence: 81%
“…The sample size was small and the cutpoint used to define sexual dysfunction was that of European societies, and could be less appropriate for our population. Studies have shown that the good quality of dialysis positively influenced the sexual functions [28] and having only two sessions of dialysis may have overestimated the prevalence in our population. We couldn't correlate the dysfunction with the quality of dialysis.…”
Section: Discussionmentioning
confidence: 92%
“…As the model included adjustment for patient's weight, these associations were independent of the gender and race weight differences. The association of race [27,28,29,30,31] and gender [32,33,34,35] with QOL in HD patients have long been noted. These may be secondary to spiritual beliefs [28], social factors [31,] psychological factors [29,34,35], how different genders or ethnic groups perceive their health level, or to different health expectations [30].…”
Section: Discussionmentioning
confidence: 99%
“…Sobre o aparecimento dessa sintomatologia psiquiátrica, pesquisas revelaram que os níveis de depressão e sintomas psicológicos além de distúrbios de ansiedade são mais frequentes e mais intensos em mulheres portadoras de DRC e em tratamento hemodialítico 22,26 . As narrativas mostraram que as longas horas de sessões de hemodiálise, a cronicidade do tratamento somado à incerteza de uma cura, conferia a estas pacientes características como medo do futuro, valorização do presente, angústia e pouca perspectiva diante de projetos em longo prazo.…”
Section: Discussionunclassified